Economy and Society: An Outline of Interpretive Sociology. Organized Groups (an excerpt) - Weber, Max; IoninL. G. (Journal of Economic Sociology, 2017)
This book presents the second volume of Max Weber’s fundamental work Economy and Society, which has been translated into Russian for the first time. The second volume “Organized Groups” uncovers emerging and crystallizing structures of rationality governing how organized groups function during different periods in their history. Concepts such as households, oikos, and ethnic groups and political associations (including parties and state), are defined here. The Journal of Economic Sociology publishes an excerpt from one of the chapters of the second volume “Organized Groups” — ‘Economic Relationships of Organized Groups.’ This chapter introduces economic action and economically active groups; it classifies organized groups according to their group structure and economic function. It also explains the concept of closed and open economic relationships. In conclusion, it analyzes five types of want satisfaction by economically active groups, resulting in the question of which of those types most closely corresponds to a rational capitalistic economy. The translation is edited by Leonid Ionin. The chapter is published with the permission of HSE Publishing House.